In Spite of Curative Radical Pulmonary Procedures, Lesser Pulmonary Resection Shows More Favorable Prognosis in Surgically Treated NSCLC With Synchronous Isolated Cranial Oligometastases - Kaba, Erkan; Yardımcı, Eyüp Halit; Kakuturu, Jahnavi; Toker, Alper (Frontiers in Surgery, 2021)
Oligometastatic disease in lung cancer is not a rare condition as previously thought. Among 812 non-small cell lung cancer patients treated surgically with lung resection between October 2011 and October 2018 at the Department of Thoracic Surgery, Florence Nightingale Hospitals, Turkey, 28 patients (3.4%) had synchronous cranial metastases. We analyzed synchronous isolated cranial metastases patients treated by locally ablative treatments (surgery, radiotherapy, or both). Metastases existing at the diagnosis of primary cancer were considered as synchronous, and their treatment was performed before (at least 1 month) or after (for maximum 1 month) surgery of the primary lung lesion. Prognostic factors affecting survival are evaluated retrospectively to identify clinical factors predicting survival in an effort to better select patients for surgery. Patients having T1-T2 primary lung tumors, no mediastinal lymph node metastasis, receiving minor anatomical lung resection, receiving neoadjuvant chemotherapy, having single cranial metastasis, and receiving surgical cranial metastasectomy were found to have better survival. According to tumor histology, having adenocarcinoma, and not having lymphovascular or visceral pleura invasion correlated with better survival. Average survival time was 52.1 months and median survival was 32 months. The last mortality during the follow-up was at 24 months; cumulative survival was 48.3% at that time. Our study was designed to define the criteria for patients with oligometastatic disease who may benefit from lung resection.